Interactions of hydrated IIa and IIb group metal cations with thioguanine-cytosine DNA base pair: Ab initio and density functional theory investigation of polarization effects, differences among cations, and flexibility of the cation hydration shell - Sponer, J; Burda, J V; Leszczynksi, J; Hobza, P (Journal of biomolecular structure & dynamics, 1999)
The structures and energies of the thioguanine-cytosine Watson-Crick (thioGC WC) base pair interacting with hydrated IIa (Mg2+, Ca2+, Ba2+) and IIb group (Zn2+, Cd2+, Hg2+) cations have been studied using ab initio techniques. Furthermore, complexes between guanine and thioguanine with hydrated cations have been characterized assuming various structures of the hydration shells. The complexes of the thioGC WC base pair with hydrated cations have similar properties as the previously studied GC WC base pair. There is substantial polarization stabilization of the base pairing due to cation binding which amounts to 7 - 11 kcal/mol. Soft Cd2+ and Hg2+ cations have a uniquely strong interaction with the thiogroup and induce substantial nonplanarity of the pairing. The thiogroup tends to reduce the number of water molecules in the first hydration shell of the cation. All complexes were optimized within the Hartree-Fock (HF) approximation while their energetics has been evaluated using the second-order Moller-Plesset perturbational method (MP2). All interaction energy evaluations and a substantial portion of the optimizations of the hydrated cation-(thio)guanine complexes have been repeated using Becke-3LYP Density Functional Theory method. All three approximations used (HF, Becke-3LYP, and MP2) give qualitatively the same results for the present cationic complexes. The results demonstrate specific differences among the cations and provide a set of reference structures and energies for verification and/or parametrization of empirical potentials and other theoretical methods.
Keywords: Metals; hořčík; konformace nukleové kyseliny; kationty dvojmocné; cytosin; Nucleic Acid Conformation; Thioguanine; kovy; Energy Transfer; guanin; Zinc; Guanine; DNA; voda; vápník; Water; rtuť; Calcium; Mercury; Cadmium; párování bází; baryum; thioguanin; Barium; Magnesium; Base Pairing; přenos energie; kadmium; Cytosine; zinek; Cations, Divalent